Analysis Of Inside Feet Passing Techniques On Football Extracurricular Participants In Smp Negeri 21 Seluma, Seluma Regency - Sastra Ade Saputra; Feby Elra Perdima; Azizatul Banat (Sinar Sport Journal, 2021)
This study aims to analyze the technique of inner foot passing on soccer extracurricular participants at SMP Negeri 21 Seluma. The method used in this research is a survey method with data collection techniques using observation sheets, with the type of descriptive research. The population in this study were soccer extracurricular participants at SMP Negeri 21 Seluma. Sampling technique using total sampling, namely the technique of determining the sample by taking the entire population. Based on this, the sample in this study amounted to 22 participants. Data analysis used quantitative descriptive as outlined in the form of a percentage. The results showed that the analysis of the inner foot passing technique for soccer extracurricular participants at SMP Negeri 21 Seluma. The results of the overall analysis show that the analysis of the inner foot passing technique for soccer extracurricular participants at SMP Negeri 21 Seluma based on the coach's assessment obtained the value of the preparation phase of 85.4%, the implementation phase of 87.5%, follow through of 65.1% with a total of 79.3%. While the assessment of expect judgment obtained the value of the preparation phase of 83.1%, the implementation phase of 82.9%, the follow-through of 57.5% with a total of 74.5%. It can be concluded that the average percentage value based on the assessment of the coach and expert judgment is 76.9%.